Noticias botánicas colombianas, ii: especies nuevas y críticas (1943)
Orbignya Cuatrecasana Dugand, sp. nov. / Syagrus Sancona. (RBK.) Karst. / Synechanthus Warscewiczianus / Manicaria saccifera / Socratea elegans / Trichilia lamellulata Dugand, sp. nov. / Euphorbia mesembryanthemifolia / Pseudobombax subandinum Dugand, sp, nov. / Bombax obtusum / Peschiera cymosa (Jacq.) Dugand, comb. nov.